Educational Management Innovation: Challenges and Opportunities in the Digital Era - Dadang Mulyana (SEAN Institute, 2023)
In the ever-developing digital era, educational management innovation is crucial for overcoming challenges and taking advantage of emerging opportunities. This research aims to investigate the dynamics of educational management innovation, identify the challenges faced, and explore opportunities that can be utilized in facing changes in the digital era. This research methodology uses a qualitative approach with descriptive methods. The research results show that educational management innovation in the digital era has had a positive impact. The use of a Learning Management System (LMS) has succeeded in increasing the efficiency and quality of learning. Adaptive learning, VR and AR technologies provide a better learning experience. Online collaboration platforms effectively expand the learning space and develop collaborative skills. Data analytics helps institutions identify trends and improve learning strategies. Game elements in learning increase student motivation. A focus on developing digital skills through curriculum and training has proven essential. However, there are still challenges such as unequal access to technology and digital security that need to be addressed to continue to increase the effectiveness of educational innovation in the digital era.